Investigation of Reported Aflatoxin Production by Fungi Outside the Aspergillus flavus Group - Wilson, Benjamin J. (Appl Microbiol, 1968)
A screening study of 121 fungus isolates, representing 29 species, for aflatoxin synthesis demonstrated this property only in Aspergillus flavus and A. parasiticus. Eight of the organisms found negative were isolates reported by other investigators to produce aflatoxin. Since similar negative reports have come from several other workers, it is concluded that only the A. flavus group of Aspergillus can presently be certified as sources of these toxins. Reasons for possible false-positive findings are discussed along with precautionary measures and differential analytical procedures useful in aflatoxin screening studies.